Recognizing and Grading CAR T-Cell Toxicities: An Advanced Practitioner Perspective - Sievers, Savannah; Watson, Grace; Johncy, Swapna; Adkins, Sherry (Frontiers in Oncology, 2020)
Over the past decade, chimeric antigen receptor (CAR) T-cell therapy has significantly improved the outlook for many patients with relapsed and/or refractory B-cell malignancies. The use of CAR T-cell therapy and other therapeutic immune effector cells will likely continue to expand with the development of other targets and use in solid tumors. Although these therapies have shown significant promise in the treatment of some malignancies, they can be associated with unique toxicities including cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome which can be fatal if not identified early and treated appropriately. An understanding of how best to manage the toxicities associated with CAR T-cell therapy is continually evolving. Institutions providing CAR T-cell therapy have undergone changes in infrastructure and staffing models in order to safely care for patients receiving this novel therapy. As members of a multi-disciplinary health care team, advanced practice providers play significant roles in caring for this patient population and must be well versed in the recognition, grading, and appropriate management of CAR T-cell therapy-related toxicities as these providers care for patients in multiple settings across the continuum of care.